2017
DOI: 10.2298/sos1702159l
|View full text |Cite
|
Sign up to set email alerts
|

Impact of biofuel in agglomeration process on production of pollutants

Abstract: Production of agglomerate in the metallurgical company belongs among the largest sources of emissions damaging the environment. Effects of coke breeze substitution by charcoal, pine, and oak sawdust there were sintering performed in a laboratory agglomeration pan with substitution ratios of 14 % and 20 % by the emissions of CO 2 , CO, NO x and NO. Variations in the gas emissions might have been affected by physical and chemical properties of the input materials and the technological parameters of agglomeration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The effect of replacing part of solid fuel during sintering with various biomaterials is investigated. Accordingly, the study [11] of the effect of replacing coke breeze with charcoal, pine and oak sawdust is carried out. It is shown that when using sawdust materials as a solid fuel, considerable fluctuations in the process parameters are observed.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The effect of replacing part of solid fuel during sintering with various biomaterials is investigated. Accordingly, the study [11] of the effect of replacing coke breeze with charcoal, pine and oak sawdust is carried out. It is shown that when using sawdust materials as a solid fuel, considerable fluctuations in the process parameters are observed.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Production of agglomerate in the metallurgical company belongs among the largest sources of emissions damaging the environment. Effects of coke breeze substitution by charcoal, pine, and oak sawdust there were sintering performed in a laboratory agglomeration pan with substitution ratios of 14% and 20% by the emissions of CO2, CO, NOx and NO (Lesko et al 2017). Researchers in Asia (Jiang, T., et al 2010) are introducing a completely new method, known as CAP, where it involves total or partial separation of ores (8-16 mm) in a drum and the remainder of the ore is pelleted after the first mixing with the return of the return sinter fines, fuel and additives.…”
Section: Sintering Processmentioning
confidence: 99%
“…The production rate of Portland cement is at approximately 3000 Mt/year [3], and about 13500 million tons of CO2 are released in the atmosphere from this process worldwide. The main greenhouse gas is CO2, which has an essential role in increasing global warming [4][5][6]. Due to the increasing temperature around the world, greenhouse gas emissions are an  Corresponding author: Masoud Rajabi, m.rajabi@eng.ikiu.ac.ir environmental issue, and the cement industry has an important role to play in their reduction [5,7,8].…”
Section: Introductionmentioning
confidence: 99%